ҰЛТТЫҚ ЭКОНОМИКАНЫҢ БƏСЕКЕГЕ ҚАБІЛЕТТІЛІГІН ТАЛДАУ - Дуламбаева, Р Т; Калиева, А Е (Journal of Economic Research & Business Administration, 2015)
This article devoted to the topic of national competitiveness. The article deals with the concept of national competitiveness, evaluation criteria and ways of improving national competitiveness.